Surveying Smartphone Security for Linux Powered Devices (International Journal of Engineering and Computer Science, 2015)
In this era of Globalization,  the extensive use of SmartPhones in our  day-to-day  life has become a very important factor.  According  to surveys,  nearly  0.8 of the SmartPhone industry  is dominated  by Android.  Therefore, the  issue  of  Security  and  Privacy  of  the  User  becomes a  crucial  factor  to  be  taken  care  of.  Since,  Android   is an  Open-Source   Platform,   the  scope  of  resolving  issues like this becomes easy and effective with the help of applications  designed  by programmers around the  globe. Smartphones running  on  Android   OS  have  an  in-built password  detection mechanism  (character/pattern/gesture) which helps in differentiating between real user from unknown   user.  Also,  the  proposed   system  are  designed to  work  with  their   own  perspective   to  meet  the  users demands   and   this   done   with   the   help   of  pre-defined sensors  which  are  thoroughly   elaborated  after   a  lot  of search.   In  this  paper,   A  survey   of  the  research  done by  the  predecessors  on  related subject  to  provide  better security and to overcome this breach  of privacy. Now while discussing the security  measures,  The system can possibly assume  that  under  a certain  type of scenario  an intruder may try to access valuable information of the user without his knowledge  and  when  faced  with  a password  barrier, the  intruder may  try  to  bypass  it  by  entering   another password,  and  if the  password  is wrong  it may  result in multiple failed attempts.  So there has to be certain  solution to  detect  this  breach  and  if possible  overcome  it.  Along with this, the proposed  system should  make  sure  that  the application consumes  least  amount   of  battery and  uses minimum  amount  of system memory.